(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
In this article, there were examined the writing style of the talented author Bahodir Kabul, focusing on his ability to create characters and imagery. It also analyzes the codes and symbols present in his works and the principles he employs to reveal the psyche of his heroes.